2014
DOI: 10.1111/anzs.12074
|View full text |Cite
|
Sign up to set email alerts
|

Bayes Hilbert Spaces

Abstract: Summary A Bayes linear space is a linear space of equivalence classes of proportional σ‐finite measures, including probability measures. Measures are identified with their density functions. Addition is given by Bayes' rule and substraction by Radon–Nikodym derivatives. The present contribution shows the subspace of square‐log‐integrable densities to be a Hilbert space, which can include probability and infinite measures, measures on the whole real line or discrete measures. It extends the ideas from the Hilbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 22 publications
0
81
0
Order By: Relevance
“…Furthermore, we show in Sect. 3.3 that an isometric isomorphism exists between A 2 ðT Þ and L 2 ðT Þ: Additional properties and generalizations are reported in (Egozcue et al 2006;van den Boogaart et al 2010).…”
Section: Field Datamentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, we show in Sect. 3.3 that an isometric isomorphism exists between A 2 ðT Þ and L 2 ðT Þ: Additional properties and generalizations are reported in (Egozcue et al 2006;van den Boogaart et al 2010).…”
Section: Field Datamentioning
confidence: 83%
“…The problem of kriging PDFs has been considered also by Salazar Buelvas (2011), who exploits a logarithmic transformation to deal with the data constraint. Our approach is however different and move from the geostatistical methodology proposed in (Menafoglio et al 2013) and the mathematical construction developed by Egozcue et al (2006) and further investigated in (van den Boogaart et al 2010). Our approach shares with FDA and CoDa the foundational role of geometry.…”
Section: Introductionmentioning
confidence: 96%
“…This space was designed by and Van den Boogaart et al (2014) precisely to represent the salient features of density functions when interpreted in the light of compositional data analysis. For instance, the information conveyed by compositional data is well-known to be relative (Aitchison, 1986;Pawlowsky-Glahn and Egozcue, 2001), that is, the relevant information is provided by ratios between the parts (i.e., the point evaluation of the functions) rather that by the absolute value of the functions themselves.…”
Section: Sfpca Of Probability Density Curvesmentioning
confidence: 99%
“…A number of authors (e.g., , Van den Boogaart et al, 2010, Delicado (2011, Van den Boogaart et al (2014), Menafoglio et al (2014Menafoglio et al ( , 2016aMenafoglio et al ( , 2016b, Hron et al (2016)) pointed out that PDFs can be interpreted as functional compositional data, i.e., functional observations carrying only relative information, which are usually collected in the form of constrained data integrating to a constant. Traditional FDA techniques operate in the space of square-integrable real measurable functions L 2 , whereas compositional data entails the use of a different space, known as Bayes space, B 2 , Van den Boogaart et al, 2010, Egozcue et al (2013, Van den Boogaart et al (2014)), that generalizes to the functional setting the well-known Aitchison geometry for compositional data (Aitchison, 1986;Pawlowsky-Glahn and Egozcue, 2001;Egozcue, 2009;Pawlowsky-Glahn and Buccianti, 2011). Therefore, the theory of Bayes spaces can be used to extend the applicative domain of FDA techniques to probability density curves.…”
Section: Introductionmentioning
confidence: 99%
“…Bayes Hilbert spaces are spaces of measures and densities, and their algebraicgeometric structure is an extension of the Aitchison geometry of the simplex. In fact, in (Boogaart et al 2014), it is shown that the simplex, endowed with the Aitchison geometry, is a particular case of a Bayes Hilbert space. In the development of Bayes Hilbert spaces, a reference probability measure is introduced as a parameter regulating the geometry of the measures and densities in the space.…”
Section: Introductionmentioning
confidence: 99%